Integrated teaching of reading in Portuguese as an additional language (PLA) and writing in Spanish as a community language (ELC) at the university - Díaz, Damián (BELT - Brazilian English Language Teaching Journal, 2023)
A proposal for the sequencing of teaching Portuguese as an additional language (PLA) is presented in the context of a course focused on reading comprehension, located in one undergraduate course in communication at an Uruguayan university. The paper aims to discuss the analysis of some of its results. The proposal is based on the didactic sequence models of Sociodiscursive Interactionism (Dolz, et al., 2004; Magalhães & Cristovão, 2018), Gender Pedagogy (Rose, 2017; Rose & Martin, 2018), the concepts of reading to write (Flower, et al., 1990; Spivey, 1990; Asención, 2008); and integrated assessment of reading and writing (Cumming, 2013; Scaramucci, 2016). The proposal integrates teaching Portuguese for reading (through genres of circulation in the academic and professional spheres) to teaching Spanish for writing (through genres of the same groups). In the course, the necessary capacities to read the texts in PLA, write the texts in Spanish and use the read texts in PLA as sources for writing in Spanish are modelled recursively. In this article, we place or focus on the resources developed to teach the last two skills (writing commands, practice activities in the classroom, formative assessment instruments), as well as the results of their application from the qualitative (content) analysis of 38 texts produced by students with foci on evidence of appropriation of these capacities. The analysis results show the possible beneficial potential of the proposal, given the relative success of a significant number of the students in writing a text based on the given sources. Therefore, there are difficulties in understanding the importance of the information derived from recognized sources in the construction of the text, as well as the usefulness of referring to precise information in the development of the argument.